2007
DOI: 10.1136/oem.2006.032078
|View full text |Cite
|
Sign up to set email alerts
|

Gene-environment interactions in parkinsonism and Parkinson’s disease: the Geoparkinson study

Abstract: Objectives:To investigate associations of Parkinson’s disease (PD) and parkinsonian syndromes with polymorphic genes that influence metabolism of either foreign chemical substances or dopamine and to seek evidence of gene-environment interaction effects that modify risk.Methods:A case-control study of 959 prevalent cases of parkinsonism (767 with PD) and 1989 controls across five European centres. Occupational hygienists estimated the average annual intensity of exposure to solvents, pesticides and metals, (ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 25 publications
5
76
1
4
Order By: Relevance
“…A French study [274] reported that risk of PD for professional pesticide use was more than doubled in slow metabolizers compared to other individuals, whereas, in the absence of pesticide exposure, slow metabolizers had no increased risk [274]. These results were supported by an Australian study [275] but not by a European multicentre study [276].…”
Section: Susceptibility Genesmentioning
confidence: 98%
“…A French study [274] reported that risk of PD for professional pesticide use was more than doubled in slow metabolizers compared to other individuals, whereas, in the absence of pesticide exposure, slow metabolizers had no increased risk [274]. These results were supported by an Australian study [275] but not by a European multicentre study [276].…”
Section: Susceptibility Genesmentioning
confidence: 98%
“…Variations in CYP2D6 have been associated with a vast list of diseases (e.g., arterial hypertension, 12 leukemia, 13 childhood apnea, 13 thyroid cancer, 14 Alzheimer disease and Parkinson disease, [15][16][17][18][19] hepatic disease, 20 pulmonary disease, 21,22 breast cancer, 23 porphyrias 24 ) and with people's ability to metabolize antidepressants. 25 To date, up to 75 different alleles have been reported for CYP2D6 (descriptions available at www .imm.ki .se/cypalleles); more than 15 of these encode an inactive isoform or no enzyme, whereas other variations consist of gene duplications.…”
Section: Cytochrome P450mentioning
confidence: 99%
“…Among them, 17 studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] that met the inclusion criteria were involved in our meta-analyses. Among the involved studies, 3 studies for GSTP1-104 variant [26,29,31] were excluded for the deviation from HWE in controls (p < Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…GST enzymes can detoxify many oxidative products and thus lower the PD risk in the smokers [20] and the people with pesticides exposure [21]. GST genes that have been studied most in the PD association include GSTT1 [22][23][24][25][26][27][28][29][30][31][32][33] on chromosome 22q11.23, GSTM1 [22][23][24][25][26][27][28]30,[32][33][34][35][36][37][38] on chromosome 1p13.3, and GSTP1 [23,26,[28][29][30][31]33,37,38] on chromosome 11q13. The phenotypic absence of GSTM1 and GSTT1 activity is the consequences of homozygous deletion of these genes [39,40].…”
Section: Introductionmentioning
confidence: 99%